1995
DOI: 10.1136/gut.37.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Does Helicobacter pylori infection increase gastric sensitivity in functional dyspepsia?

Abstract: The role ofHelicobacterpylori infection in the pathogenesis of functional dyspepsia is debated. It is known that a substantial fraction of dyspeptic patients manifest a low discomfort threshold to gastric distension. This study investigated the symptomatic pattern in 27 Hpylori positive and 23 H pylori negative patients with chronic functional dyspepsia, and potential relations between infection and gastric hyperalgesia. Specific symptoms (pain, nausea, vomiting, bloating/fullness, early satiety) were scored f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0
5

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(75 citation statements)
references
References 18 publications
2
68
0
5
Order By: Relevance
“…93 There is also no evidence that H. pylori-infected NUD patients have altered gastric visceral perception compared with uninfected NUD controls. 94 Studies have suggested that H. pylori infection is more common in NUD patients compared with asymptomatic controls, but this is not a universal finding. A review of the literature and metaanalysis suggested H. pylori was a risk factor for NUD (odds ratio (OR), 2.3; 95% confidence interval (CI), 1.9 to 2.7), 67 but the choice of control groups in some of the studies included in the review were inappropriate.…”
Section: Evidence For the Role Of H Pylori In Nudmentioning
confidence: 99%
“…93 There is also no evidence that H. pylori-infected NUD patients have altered gastric visceral perception compared with uninfected NUD controls. 94 Studies have suggested that H. pylori infection is more common in NUD patients compared with asymptomatic controls, but this is not a universal finding. A review of the literature and metaanalysis suggested H. pylori was a risk factor for NUD (odds ratio (OR), 2.3; 95% confidence interval (CI), 1.9 to 2.7), 67 but the choice of control groups in some of the studies included in the review were inappropriate.…”
Section: Evidence For the Role Of H Pylori In Nudmentioning
confidence: 99%
“…Helicobacter pylori infection has been hypothesized to be associated with an increased postprandial gastric sensitivity in FD, although no relation between H. pylori infection and gastric hypersensitivity in humans has been established [6, 7, 8]. Experimental evidence in animals suggests that the mucosal inflammatory response associated with the infection may trigger sensitization of afferent nerve endings [5, 8].…”
Section: Introductionmentioning
confidence: 99%
“…In our microarray analysis using the stomachs of H. pyloriassociated gnotobiotic mice, the genes of the muscle cell component were also highly upregulated. The stomachs of H. pylori-infected mice exhibit inflammation, as well as disturbance in gastric emptying (15). Therefore, such abnormally thick muscle layers accompanied by inflammation may cause a failure in gastric emptying.…”
Section: Vol 77 2011 Gastrin Regulation By Lactobacilli 6969mentioning
confidence: 99%